18F‐labeled 1, 2, 3‐triazole‐linked Glu‐urea‐Lys‐based PSMA ligands have good pharmacokinetic properties for positron emission tomography imaging of prostate cancer. Issue 16 (22nd September 2020) - Lee, Byoung Se; Chu, So Young; Jung, Woon Jung; Jeong, Hyeon Jin; Lee, Kyongkyu; Kim, Min Hwan; Kim, Mi Hyun; Chi, Dae Yoon; Ahn, Heesu; Lee, Yong Jin; Lee, Kyo Chul; Lim, Sang Moo
Abstract: Background: Prostate‐specific membrane antigen (PSMA) is increasingly recognized as an excellent target for prostate cancer imaging and therapy. Finding compounds with a high target‐to‐nontarget ratio are an important challenge in the development of positron emission tomography (PET) imaging agents. In this study, we attempted to find a suitable compound from a simply‐synthesized compound library. Method: 18 F‐labeling was achieved in a two‐step synthesis consisting of [ 18 F]fluorination of azido sulfonates followed by copper(I)‐catalyzed click ligation. In vitro binding experiment and in vivo studies were carried out using isogenic PSMA+ PC3‐PIP and PSMA− PC3‐flu cells and 22RV1 cells. [ 125 I]MIP‐1095 was used to measure the binding affinities of compounds through a competitive binding assay, and [ 18 F]DCFPyL was used for a comparative assessment of compounds. Radiation dosimetry data were obtained using OLINDA/EXM software. Results: Nine novel PSMA ligands were synthesized by the combination of three azido compounds and three terminal acetylene‐containing Glu‐urea‐Lys compounds. Among them, compound 6f having a pyridine moiety showed a high binding affinity of 6.51 ± 0.19 nM ( K i ). 18 F‐labeled compounds were obtained at moderate yields within 70 to 75 minutes (including high‐performance liquid chromatography purification). Compound [ 18 F]6c had the lowest log P of −2.693. MicroPET/computed tomography (CT) images were acquired from 22RV1 cell xenograft mice after injecting [ 18 F]6c, [ 18 F]6f, and [ 18 F]6i . Additional microPET/CT experiments of [ 18 F]6c and [ 18 F]6f were performed using PSMA+ PC3‐PIP and PSMA− PC3‐flu cell‐bearing mice. [ 18 F]6c was selected for further studies because it was found to have high uptake in tumors and rapid renal clearance, resulting in great tumor‐to‐nontumor ratios and distinct tumor images with very low background activity. Human dosimetry estimation of [ 18 F]6c using OLINDA/EXM software was calculated, resulting in an effective dose of 4.35 × 10 −3  mSv/MBq. Conclusions: [ 18 F]6c showed significant tumor uptake, a high tumor‐to‐nontumor ratio, and good radiation dosimetry results, suggesting further development as a potential diagnostic PET agent for prostate cancer.